Fine mapping of Rf2, a major locus controlling pollen fertility restoration in sorghum A1 cytoplasm, encodes a PPR gene and its validation through expression analysis. (12th March 2018) - Madugula, Praveen; Uttam, Anurag G.; Tonapi, Vilas A.; Ragimasalawada, Madhusudhana
Abstract: Sorghum is one of the pioneering cereal crops where cytoplasmic male sterility (CMS) was successfully exploited for mass production of F1 hybrid seed. Mapping genes for fertility restoration ( Rf ) is an important aspect of understanding the molecular basis of fertility restoration in crop plants. In this study, we fine‐mapped a fertility restoration locus, Rf2 of sorghum reported earlier (Jordan, Mace, Henzell, Klein, & Klein, 2010 ), involving two F2 populations (296A × RS29 and 296A × DSV1) and newly developed SSR markers delimited Rf2 locus to 10.32‐kb region on chromosome 2. The Rf2 locus was tightly linked with two new SSRs, MS‐SB02‐3460 (0.14 cM) and MS‐SB02‐3466 (0.75 cM) on both sides, and hosted only one gene ( Sobic.002G057050 ) of PPR gene family. Another new SSR marker developed in the study, MS‐SB02‐37912, forms the part of PPR gene and could act as a perfect marker in marker‐assisted breeding for fertility restoration involving Rf2 in sorghum breeding. The strong involvement of Sobic.002G057050 gene in fertility restoration was supported through RNA expression analysis.